Mortality in women of reproductive age in rural South Africa - Nabukalu, Dorean; Klipstein-Grobusch, Kerstin; Herbst, Kobus; Newell, Marie-Louise (Global Health Action, 2013)
Objective: To determine causes of death and associated risk factors in women of reproductive age in rural South Africa. Methods: Deaths and person-years of observation (pyo) were determined for females (aged 15 49 years) resident in 15,526 households in a rural South African Demographic and Health Surveillance site from 2000 to 2009. Cause of death was ascertained by verbal autopsy and ICD-10 coded; causes were categorized as HIV/TB, non-communicable, communicable/maternal/perinatal/nutrition, injuries, and undetermined (unknown). Characteristics of women were obtained from regularly updated household visits, while HIV and self-reported health status was obtained from the annual HIV surveillance. Overall and cause-specific mortality rates (MRs) with 95% confidence intervals (CI) were calculated. TheWeibull regression model (HR, 95% CI) was used to determine risk factors associated with mortality. Results: A total of 42,703 eligible women were included; 3,098 deaths were reported for 212,607 pyo. Overall MRwas 14.6 deaths/1,000 pyo (95% CI: 14.1 15.1), peaking in 2003 (MR 18.2/1,000 pyo, 95% CI: 16.4 20.1) and declining thereafter (2009: MR 9.6/1,000 pyo, 95% CI: 8.4 10.9). Mortality was highest for HIV/TB (MR 10.6/1,000 pyo, 95% CI: 10.2 11.1), accounting for 73.1% of all deaths, ranging from 61.2% in 2009 to 82.7% in 2002. Adjusting for education level, marital status, age, employment status, area of residence, and migration, all-cause mortality was associated with external migration (adjusted hazard ratio, or aHR), 1.70, 95% CI: 1.41 2.05), self-reported poor health status (aHR 8.26, 95% CI: 2.94 23.15), and HIV-infection (aHR 7.84, 95% CI: 6.26 9.82); external migration and HIV infection were also associated with causes of mortality other than HIV/TB (aHR 1.62, 95% CI: 1.12 2.34 and aHR 2.59, 95% CI: 1.79 3.75). Conclusion: HIV/TB was the leading cause of death among women of reproductive age, although rates declined with the rollout of HIV treatment in the area from 2004. Women’s age, external migration status and HIV-positive status were significantly associated with all-cause and cause-specific mortality.